Research on Simulation and Optimization of Production Line Based on Flexsim - Wei Liu, Jiaxing Lin (Forest Chemicals Review, 1970)
As China proposes to accelerate the construction of a new development pattern with the domestic cycle as the main body and the domestic and international dual cycles promoting each other, the coastal manufacturing industry, which has long been developed by relying on foreign trade exports, urgently needs to transform into regional development and transformation dominated by the internal cycle. In this paper, through field research and interviews on a cosmetic organizer assembly line in company Z, We analyzed the process and work elements of the mirror production line of storage boxes. We measured the work time and found the bottleneck process based on this. Then we used Flexsim to simulate the production line and analyze the three indexes of in-process time, idle time, and blockage time. We found that there were problems such as low balance rate of the production line and the large load gap between processes. The method and tools are used to optimize and improve the production line's process flow and bottleneck process and carry out the simulation verification again. To further improve the production line, this article combines the 6S management method to improve the on-site management of Z company. We establish a responsible organization to supervise, and we strengthen training to improve employees' responsibility; in the end, we plan the placement of on-site items. It has a significant reference value for the same type of enterprise to achieve production line balance.